Inhibition of the NLRP3 Inflammasome Activation by Manoalide Ameliorates Experimental Autoimmune Encephalomyelitis Pathogenesis - Li, Cong; Lin, Hualong; He, Hongbin; Ma, Ming; Jiang, Wei; Zhou, Rongbin (Frontiers in Cell and Developmental Biology, 2022)
The activation of NLRP3 inflammasome leads to cell pyroptosis and inflammatory cytokines secretion and gets involved in the development of many diseases, such as neuroinflammation and metabolic syndrome, but the drugs targeting NLRP3 are notclinically available for now. Through screening the small molecule library, we found that manoalide is a highly selective small molecule inhibitor of NLRP3. Mechanismly, manoalide inhibited the NLRP3 inflammasome activation by acting downstream of potassium efflux, chloride efflux and mitochondrial dysfunction. Moreover, manoalide blocked the interaction between NEK7 and NLRP3 by covalently binding to Lys 377 of the NLRP3 protein. Treatment of manoalide relieved the pathogenesis of experimental autoimmune encephalomyelitis (EAE) in mice. Thus, our results identify manoalide as a selective and covalent NLRP3 inhibitor and suggest it has the potential for the treatment of NLRP3-associated diseases.